Analysis of aggregated inflation expectations based on the ECB SPF survey - Sami Oinonen; Maritta Paloviita (Bank of Finland, 2014)
This paper examines aggregated inflation expectations based on the ECB Survey of Professional Forecasters (ECB SPF). We analyse possible impacts of changing panel composition on short and long term point forecasts and forecast uncertainties using approach, which is based on a set of sub-panels of fixed composition. Our results indicate that the unbalanced panel data do not cause systematic distortions to aggregated survey information. However, micro level analysis of expectations would also be useful, especially in times of wide disagreement across forecasters and high levels of inflation uncertainty.
URN:NBN:fi:bof-201412193439
Keywords: C53; E37; E31; 330; survey data; expectations; changing panel composition